The Chromatin Remodeler Brg1 Integrates ROS Production and Endothelial-Mesenchymal Transition to Promote Liver Fibrosis in Mice - Li, Zilong; Chen, Baoyu; Dong, Wenhui; Kong, Ming; Shao, Yang; Fan, Zhiwen; Yu, Liming; Wu, Dongmei; Lu, Jun; Guo, Junli; Xu, Yong (Frontiers in Cell and Developmental Biology, 2019)
Trans-differentiation of endothelial cells to myofibroblast contributes to liver fibrosis. Reactive oxygen species (ROS) plays a key role in endothelial-mesenchymal transition (EndMT) although the underlying epigenetic mechanism is unclear. Here we report that endothelial conditional knockout of BRG1, a chromatin remodeling protein, attenuated liver fibrosis in mice. BRG1 deficiency in endothelial cells was paralleled by a decrease in ROS production and blockade of EndMT both in vivo and in vitro. The ability of BRG1 to regulate ROS production and EndMT was abolished by NOX4 depletion or inhibition. Further analysis revealed that BRG1 interacted with SMAD3 and AP-1 to mediate TGF-b induced NOX4 transcription in endothelial cells. Mechanistically, BRG1 recruited various histone modifying enzymes to alter the chromatin structure surrounding the NOX4 locus thereby activating its transcription. In conclusion, our data uncover a novel epigenetic mechanism that links NOX4-dependent ROS production to EndMT and liver fibrosis. Targeting the BRG1-NOX4 axis may yield novel therapeutics against liver fibrosis.